2022
DOI: 10.1007/s00062-022-01236-0
|View full text |Cite
|
Sign up to set email alerts
|

Exact Basilar Artery Occlusion Location Indicates Stroke Etiology and Recanalization Success in Patients Eligible for Endovascular Stroke Treatment

Abstract: Introduction Endovascular stroke treatment (EST) is commonly performed for acute basilar artery occlusion (BAO). We aimed to identify the role of the exact location of BAO in patients receiving EST regarding the stroke etiology, recanalization success and prediction of favorable clinical outcome. Methods Retrospective analysis of 191 consecutive patients treated for BAO with EST from 01/2013 until 06/2021 in a tertiary stroke center. Groups were defined ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…proximal and middle BAO (27% and 23%) even though the difference was not statistically signi cant (P = 0.093). 7 However, it is important to note that Mutke et al employed a distinct classi cation method for the BAO location to that used in our study and did not exclude patients with mild stroke from their analysis who are less likely to bene t from EVT. 5,7 The differences in methodology may explain why in the study of Mutke et al, the BAO location did not have a signi cant impact on the clinical outcome.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…proximal and middle BAO (27% and 23%) even though the difference was not statistically signi cant (P = 0.093). 7 However, it is important to note that Mutke et al employed a distinct classi cation method for the BAO location to that used in our study and did not exclude patients with mild stroke from their analysis who are less likely to bene t from EVT. 5,7 The differences in methodology may explain why in the study of Mutke et al, the BAO location did not have a signi cant impact on the clinical outcome.…”
Section: Discussionmentioning
confidence: 98%
“…These ndings were in line with those published in previous studies. 7,[15][16][17][18] In such cases, a longer intraoperative procedure may increase the risk of damaging the vascular endothelium and eventually lead to platelet activation, reformation of the thrombus, and, ultimately, occlusion. 19 In our study, 50.9% and 62.7% of cases in the proximal and middle occlusion groups, respectively, required rescue therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The site of occlusion is also linked to the underlying etiology, since embolic stroke will more frequently involve the distal basilar artery, whereas proximal BAO is usually linked to atherosclerotic lesions of the vertebrobasilar junction. These differences also have treatment implications, since it has been shown that recanalization rates are higher in patients with distal BAO occlusions [ 28 ]. Furthermore, among all stroke subtypes, adjunctive pharmacotherapy, such as antiplatelet agents and anticoagulants, either in the acute–subacute phase or as secondary stroke prevention measures, may inherently influence the efficacy and safety following acute reperfusion therapies [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although thromboembolism is a more common cause of ischemic stroke with large and medium size vessel occlusion in the anterior circulation, the underlying etiology of basilar artery occlusion is often associated with cardioembolism, large artery atherosclerosis, and other mechanisms such as dissection and vasculopathy (Buchman & Merkler, 2019 ). Importantly, basilar artery occlusion stemming from atherosclerotic disease tends to be linked with unfavorable clinical outcomes (Lee et al., 2017 ; Mutke et al., 2023 ). During a basilar artery occlusion, atherosclerotic occlusions are commonly observed in proximal locations, whereas thromboembolic occlusions tend to occur more frequently in distal locations (Mutke et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%